Traumatic Fracture: Dislocation of Cervicothoracic Junction—Grand Round Presentation of C7-T1 Instabilities and Different Instrumentation Techniques - Mohammad A. Alsofyani; Soufiane Ghailane; Sultan Alsalmi; Sreenath Jakinapally; Louis Boissière; Ibrahim Obeid; Jean-Marc Vital (Case Reports in Orthopedics)
Introduction. Acute traumatic cervicothoracic junction spinal lesions are rare disorders and poorly documented. We report a case of a traumatic cervicothoracic fracture-dislocation. We present our experience in the operative treatment of an unstable fracture-dislocation at the cervicothoracic junction. Materials and Method. A seventy-year-old man was transferred to our hospital. We found paresthesia in the corresponding dermatome of C7 and C8 bilaterally. Initial CT scan shows vertebral body fracture of T1 with retropulsion into the spinal canal and anteroposterior dislocation of cervicothoracic junction type C according to AOSpine subaxial injury. Traumatic disc material at C7-T1 was removed by anterior cervical discectomy and fusion of C6-T2. Fixation was done from C6 to T2 in the prone position. Results. At one-year postoperative follow-up, radiographs revealed bony fusion at the level of C7-T1, and the patient had no major functional disability. Conclusion. We opted for the ventral-dorsal approach in our case for maximum stabilization and to prevent mechanical complications.